Efektivitas Program Sekolah Ramah Anak Dalam Mengembangkan Sekolah Berkarakter - Iskandar, Dodi; Yuni Hendrowati, Tri; Siswoyo, Siswoyo (Manajemen Pendidikan, 2024)
The purpose of this study is to decrypt the implementation of the Child Friendly School program and develop the character of students at SD Negeri 1 Pulaupanggung Tanggamus. This study provides a comprehensive overview of child-friendly school programs. The child-friendly program is not just a program at SD Negeri 1 Pulaupanggung but the importance of a child-friendly seklah program for student character building since elementary school. This study intends to find an overview of child-friendly school programs both in terms of supporters and obstacles.at SD Negeri 1 Pulaupanggung This type of research is descriptive qualitative in assessing field phenomena that occur. The implementation of child-friendly school programs is carried out by means of interviews, observations, and documentation. The implementation of child-friendly programs is carried out in 4 steps, namely: (1) Child-friendly school policy programs; (2) Educators and education personnel trained in children's rights; (3) Implementation of a child-friendly learning process, the application of non-violent discipline; and a safe, comfortable and clean school environment; (4) Student participation in learning. Child-friendly school policy programs include programs carried out in collaboration with students in the classroom, for example, teachers as role models should not commit violence against students or set an example in front of students. Educators and education personnel must understand the rights that must be obtained by students, if educators do not understand educators must attend related trainings. The implementation of child-friendly learning processes both in the classroom and outdoors is mandatory in accordance with the rules and policies of child-friendly school programs. Student participation in learning will increase because students feel safe and comfortable when studying so that achievements will be highlighted by students.